COMMUNITY SERVICE THROUGH STRENGTHENING UMKM: A REAL CONTRIBUTION TO VILLAGE PROGRESS - Silvia Ekasari (JOURNAL OF COMMUNITY DEDICATION, 2024)
Community service through strengthening MSMEs is an effective strategy to encourage village progress. MSMEs have a crucial role in increasing local employment, which leads to a reduction in unemployment and an increase in the income of rural communities. In addition, the economic diversification resulting from the development of various business sectors helps create village economic resilience. Through empowerment and training, the capacity of human resources in the village increases, making MSME actors more competitive and efficient. Overall, strengthening MSMEs through community service programmes not only provides short-term benefits but also opens up opportunities for sustainable and inclusive economic growth in villages.